Psychometric validation of the humor styles questionnaire among Indonesian pre-service teachers - Ali Rachman; Noorhapizah Noorhapizah; Yogi Prihandoko; Nahdia Fitri Rahmaniah (Institute of Advanced Engineering and Science, 2026)
This study aimed to develop and validate the Indonesian version of the humor styles questionnaire (HSQ-ID) for use in pre-service teacher education. A cross-sectional psychometric design was applied to a sample of 729 Indonesian pre-service teachers, using systematic translation, content validation, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA) with the robust maximum likelihood (ML) estimator. HSQ-ID showed a stable four-factor structure, strong model fit (comparative fit index (CFI)=0.97, root mean square error of approximation (RMSEA)=0.045, standardized root mean square residual (SRMR)=0.040), and acceptable internal consistency across all subscales (Cronbach α=0.72–0.89). One-way analysis of variance (ANOVA) indicated significant differences in humor styles across 10 teacher specialization fields, suggesting that humor use is shaped by disciplinary and professional training contexts. These findings confirm that the HSQ-ID is a valid and reliable instrument for evaluating humor styles in Indonesian teacher education and can support future assessment-based pedagogical interventions.